The effectiveness of a program based on integrated education in the development of self-learning skills in physics applied study on secondary school students in public schools in Karak - Al-qatawneh, Eman Mohammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the effectiveness of a program based on integrated education in the development of self-learning skills in physics among secondary school students in public schools in the province of Karak, the study adopted a semi-experimental research methodology, where two groups were selected experimental group taught through integrated education And the control group was taught according to the usual method, by 30 students per group.The most important results of the study were the existence of a significant level of effectiveness of a program based on integrated learning in the development of self-learning skills in physics in public schools in Karak governorate. The presence of statistically significant differences (α = 0,05) in self-learning skills physics students in secondary school on self-learning attributable to the method of education (combined education, regular method). It was in favour of the group that studied using integrated education. In light of the results, the study recommended the need to activate the integrated education in schools in the province of Karak, especially in scientific lessons such as physics, and also recommended to conduct training for teachers to develop teaching skills through integrated education.
Keywords: Integrated Education; Self-Learning; Physics; Secondary School